Biofilm development in three-dimensional models infected with Trichophyton rubrum - Mendonça, Matheus Bordoy [UNESP]; Cabral, Ana Karla Lima Freire [UNESP]; Arantes, Bruno Bulgarelli Adorno [UNESP]; dos Santos, Rafaela Cristine [UNESP]; Medina-Alarcón, Kaila Petronila [UNESP]; dos Santos, Kelvin Sousa [UNESP]; De Lima Gualque, Marcos William [UNESP]; de Souza Fernandes, Lígia [UNESP]; Belizario, Jenyffie Araujo [UNESP]; Fuzinaga, Thais Yume Toriy; Kawakami, Camila Martins; Gluzezak, Ana Julia Pasuch; et al. (American Society for Microbiology, 2025)
Dermatophytes are keratinophilic filamentous fungi that cause dermatophytosis, and the main etiological agents can be anthropophilic and zoophilic. Several virulence factors are involved in the pathogenesis of dermatophytosis, including the formation of fungal biofilms. In this context, three-dimensional (3D) models, such as spheroids and reconstructed human skin (RHS), have gained prominence, as they more accurately emulate fungus-host interactions, closely resembling physiological conditions. Therefore, the present study investigated the biofilm formation of Trichophyton rubrum in these 3D models using confocal microscopy, scanning electron microscopy, and relative gene expression analysis via real-time PCR. Microscopic analyses revealed the colonization of the spheroid and 3D skin model surface by T. rubrum, with characteristics indicative of biofilm formation. The gene expression analysis of the infected 3D skin model revealed an exacerbated expression of Mep5, which encodes a metalloprotease in T. rubrum, known for its keratinolytic activity. This study demonstrates biofilm formation and protease gene expression during dermatophyte infections using 3D models that contribute to understanding the mechanisms of T. rubrum infection and support the ongoing search for the development of new drugs to treat dermatophytosis.IMPORTANCEFungal skin infections, particularly those caused by dermatophytes like Trichophyton rubrum, are widespread and often neglected, resulting in significant health burdens and the development of antifungal resistance due to their virulence factors, such as biofilm formation. Traditional in vitro and ex vivo infection models fail to mimic the human skin environment accurately, lacking key features, such as keratinization and three-dimensional (3D) configuration, which are critical for emulating in vivo infection conditions. The development of alternative 3D models, such as reconstructed human skin and spheroids, presents a transformative opportunity to enhance our understanding of host-parasite interactions. These models more closely replicate the structural and physiological properties of human skin, enabling the observation of fungal invasion and biofilm behavior under more realistic conditions. By supporting complex cellular communication and maintaining tissue architecture, 3D models provide a more accurate platform for studying fungal pathogenesis, ultimately paving the way for identifying new therapeutic targets and improving strategies to combat persistent and drug-resistant infections.